COMPARATIVE STUDY OF GREEN AUDITS OF DIFFERENT EDUCATIONAL BUILDINGS - Sulakhe Prachi Pradiprao; Dr. A. C. Attar (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Now a days ‘Global Warming’ is one of thebiggest issue faced by world. Due to Environmental changes depletion; of natural resources occurs. To solve this issue; flexible, secure, dynamic infrastructure has to be devised. The purpose of the audit was to ensure the practices followed in the campus are in accordance to save the environment or not, therefore, it is essential to explain the conceptual framework of Green Audit. In these research limitations of a green audit, systems are given. After a study, we came to know that there should be quantification for green audit. In this study five green auditreports were analysed and important factors which are affecting highly on the green audit were identified.